CXCL5 mediates UVB irradiation-induced pain. - Dawes, John M; Calvo, Margarita; Perkins, James Richard; Paterson, Kathryn J; Kiesewetter, Hannes; Hobbs, Carl; Kaan, Timothy K.Y.; Orengo, Christine A.; Bennett, David LH; McMahon, Stephen B (AAAS, 2011)
Many persistent pain states (pain lasting for hours, days, or longer) are poorly treated because of the limitations of existing therapies. Analgesics such as nonsteroidal anti-inflammatory drugs and opioids often provide incomplete pain relief and prolonged use results in the development of severe side effects. Identification of the key mediators of various types of pain could improve such therapies. Here, we tested the hypothesis that hitherto unrecognized cytokines and chemokines might act as mediators in inflammatory pain. We used ultraviolet B (UVB) irradiation to induce persistent, abnormal sensitivity to pain in humans and rats. The expression of more than 90 different inflammatory mediators was measured in treated skin at the peak of UVB-induced hypersensitivity with custom-made polymerase chain reaction arrays. There was a significant positive correlation in the overall expression profiles between the two species. The expression of several genes [interleukin-1β (IL-1β), IL-6, and cyclooxygenase-2 (COX-2)], previously shown to contribute to pain hypersensitivity, was significantly increased after UVB exposure, and there was dysregulation of several chemokines (CCL2, CCL3, CCL4, CCL7, CCL11, CXCL1, CXCL2, CXCL4, CXCL7, and CXCL8). Among the genes measured, CXCL5 was induced to the greatest extent by UVB treatment in human skin; when injected into the skin of rats, CXCL5 recapitulated the mechanical hypersensitivity caused by UVB irradiation. This hypersensitivity was associated with the infiltration of neutrophils and macrophages into the dermis, and neutralizing the effects of CXCL5 attenuated the abnormal pain-like behavior. Our findings demonstrate that the chemokine CXCL5 is a peripheral mediator of UVB-induced inflammatory pain, likely in humans as well as rats.
https://v2.sherpa.ac.uk/id/publication/11116?template=romeo
Keywords: Piel - Lesiones y heridas; Radiación solar; Dolor; Calcium / metabolism; Chemokine CXCL5; Cytokines; Pain Measurement; Skin / immunology; Skin / radiation effects; Pain measurement; Ultraviolet rays / adverse effects